2021
DOI: 10.1021/acs.nanolett.1c00336
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Thermal Transport within and between Carbon Nanotubes

Abstract: Despite the excellent thermal properties of individual carbon nanotubes (CNTs), the thermal characteristics of macroscopic CNT assemblies are poor. This is probably due to the presence of numerous nontrivial intertube boundaries. Currently, clarity on the inherent difference between intra-and inter-CNT thermal conductivities is not well-established. Herein, we report an in situ nanoscale observation on the anisotropic thermal transport of a single bundle of CNTs by monitoring evaporated gold nanoparticles as "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For example, Inoue et al reported the thermal and electrical conductivities of a sheet of aligned MWCNTs as follows: 70 W m −1 K −1 and 4 × 10 4 S m −1 along the direction parallel to the nanotube axial direction, but 8.6 W m −1 K −1 and 5.5 × 10 3 S m −1 along the per-pendicular direction. 11 Even for a bundle consisting of closepacked CNTs, decrements in conductivity 7,12 and conductivity anisotropy 13 have been experimentally detected. These findings indicate that the conductivity reductions cannot be solely attributed to the spacing within assemblies and that the difference between intratube and intertube bondings in assemblies is rather important.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Inoue et al reported the thermal and electrical conductivities of a sheet of aligned MWCNTs as follows: 70 W m −1 K −1 and 4 × 10 4 S m −1 along the direction parallel to the nanotube axial direction, but 8.6 W m −1 K −1 and 5.5 × 10 3 S m −1 along the per-pendicular direction. 11 Even for a bundle consisting of closepacked CNTs, decrements in conductivity 7,12 and conductivity anisotropy 13 have been experimentally detected. These findings indicate that the conductivity reductions cannot be solely attributed to the spacing within assemblies and that the difference between intratube and intertube bondings in assemblies is rather important.…”
Section: Introductionmentioning
confidence: 99%
“…The high photothermal conversion efficiency of CNTs and the formation of laminated CNT networks enabled the self-assembled textile to have excellent photothermal conversion properties. As shown in Figure a, simulating the standard sunlight for the photothermal conversion test of textiles with different assembly times, the surface temperature of (PSS/CNTs) 3 -CT can reach 94 °C within 2 min under 1.0 sun (1 kW/m 2 ). The surface temperature of (PSS/CNTs) 7 -CT can reach 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 A series of exciting and impressive efforts have been conducted, however, these endeavors mainly focus on the in-situ electrical properties measurement in TEM. [29][30][31] A few insitu thermal measurements in TEM include the qualitative observation of anisotropic thermal transport in a CNT bundle by monitoring the phase change of gold nanoparticles as thermo-markers, 32 and the nanoscale temperature detection with a well-designed nano-thermocouple assembled in TEM. 33 However, these methods are not suitable for the quantitative thermal conductivity measurement of individual nanomaterials.…”
Section: Main Textmentioning
confidence: 99%